Maternal education and cognitive development in 15 European very-preterm birth cohorts from the RECAP Preterm platform. (15th September 2021) - Sentenac, Mariane; Benhammou, Valérie; Aden, Ulrika; Ancel, Pierre-Yves; Bakker, Leonhard A; Bakoy, Hannah; Barros, Henrique; Baumann, Nicole; Bilsteen, Josephine Funck; Boerch, Klaus; Croci, Ileana; Cuttini, Marina; et al.
Abstract: Background: Studies are sparse and inconclusive about the association between maternal education and cognitive development among children born very preterm (VPT). Although this association is well established in the general population, questions remain about its magnitude among children born VPT whose risks of medical and developmental complications are high. We investigated the association of maternal education with cognitive outcomes in European VPT birth cohorts. Methods: We used harmonized aggregated data from 15 population-based cohorts of children born at <32 weeks of gestational age (GA) or <1500 g from 1985 to 2013 in 13 countries with information on maternal education and assessments of general development at 2–3 years and/or intelligence quotients between 4 and 15 years. Term-born controls (≥37 weeks of GA) were available in eight cohorts. Maternal education was classified as: low (primary/lower secondary); medium (upper secondary/short tertiary); high (bachelor's/higher). Pooled standardized mean differences (SMDs) in cognitive scores were estimated (reference: high educational level) for children assessed at ages 2–3, 4–7 and 8–15 years. Results: The study included 10 145 VPT children from 12 cohorts at 2–3 years, 8829 from 12 cohorts at 4–7 years and 1865 children from 6 cohorts at 8–15 years. Children whose mothers had low, compared with high, educational attainment scored lower on cognitive measures [pooled unadjusted SMDs: 2–3 years = −0.32 (95% confidence intervals: −0.43 to −0.21); 4–7 years = −0.57 (−0.67; −0.47); 8–15 years = −0.54 (−0.72; −0.37)]. Analyses by GA subgroups (<27 vs ≥27 weeks) in children without severe neonatal morbidity and term controls yielded similar results. Conclusions: Across diverse settings and regardless of the degree of prematurity, low maternal education was associated with lower cognition.